Adding stable carbon isotopes improves model representation of the role of microbial communities in peatland methane cycling. (13th June 2017) - Deng, Jia; McCalley, Carmody K; Frolking, Steve; Chanton, Jeff; Crill, Patrick; Varner, Ruth; Tyson, Gene; Rich, Virginia; Hines, Mark; Saleska, Scott R.; Li, Changsheng
Abstract: Climate change is expected to have significant and uncertain impacts on methane (CH4 ) emissions from northern peatlands. Biogeochemical models can extrapolate site‐specificCH4 measurements to larger scales and predict responses of CH4 emissions to environmental changes. However, these models include considerable uncertainties and limitations in representing CH4 production, consumption, and transport processes. To improve predictions of CH4 transformations, we incorporated acetate and stable carbon (C) isotopic dynamics associated with CH4 cycling into a biogeochemistry model, DNDC. By including these new features, DNDC explicitly simulates acetate dynamics and the relative contribution of acetotrophic and hydrogenotrophic methanogenesis (AM and HM) to CH4 production, and predicts the C isotopic signature (δ 13 C) in soil C pools and emitted gases. When tested against biogeochemical and microbial community observations at two sites in a zone of thawing permafrost in a subarctic peatland in Sweden, the new formulation substantially improved agreement with CH4 production pathways and δ 13 C in emitted CH4 (δ 13 C‐CH4 ), a measure of the integrated effects of microbial production and consumption, and of physical transport. We also investigated the sensitivity of simulated δ 13 C‐CH4 to C isotopic composition of substrates and, to fractionation factors for CH4 production (αAM and αHM ), CH4 oxidation (αMO ), and plant‐mediated CH4 transport (αTP ). The sensitivity analysis indicated that the δ 13 C‐CH4 is highly sensitive to the factors associated with microbial metabolism (αAM, αHM, and αMO ). The model framework simulating stable C isotopic dynamics provides a robust basis for better constraining and testing microbial mechanisms in predicting CH4 cycling in peatlands. Key Points: A biogeochemical model has been improved to simulate relative importance of CH4 production pathways and stable carbon (C) isotopic dynamics The ability to model stable C isotopic dynamics can better constrain simulations of the individual processes in CH4 transformations The model has been tested against the observed CH4 fluxes, CH4 production pathways, and C isotopic signature of CH4 in a northern peatland